2013
DOI: 10.1186/1748-5908-8-143
|View full text |Cite
|
Sign up to set email alerts
|

A systems-based partnership learning model for strengthening primary healthcare

Abstract: BackgroundStrengthening primary healthcare systems is vital to improving health outcomes and reducing inequity. However, there are few tools and models available in published literature showing how primary care system strengthening can be achieved on a large scale. Challenges to strengthening primary healthcare (PHC) systems include the dispersion, diversity and relative independence of primary care providers; the scope and complexity of PHC; limited infrastructure available to support population health approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 45 publications
1
73
0
Order By: Relevance
“…Indeed, the significant proportion of rural research that is about Indigenous health is appropriate and very welcome. High‐quality, rurally focussed and located research helps to build the rural health sector's capacity and has been demonstrated to bring positive health service and cost outcomes 13, 14. Research that improves rural service delivery and that addresses the underlying causes of poor health can make a critical contribution to the reduction of rural health inequality, a key aim of the Australian Government.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the significant proportion of rural research that is about Indigenous health is appropriate and very welcome. High‐quality, rurally focussed and located research helps to build the rural health sector's capacity and has been demonstrated to bring positive health service and cost outcomes 13, 14. Research that improves rural service delivery and that addresses the underlying causes of poor health can make a critical contribution to the reduction of rural health inequality, a key aim of the Australian Government.…”
Section: Discussionmentioning
confidence: 99%
“…System‐wide quality improvement is an effective method to strengthen health systems and enhance provision of quality care 41 . Primary health care networks and partnership‐based approaches to quality improvement, such as the ABCD National Research Partnership, can be used to strengthen quality of primary health care to address inequitable levels of chronic disease experienced by Indigenous people 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…Special challenges arise in systems-based research, including the need to navigate across the various layers of departments and disciplines and engage stakeholders at multiple levels in the organization. 24 As the largest integrated health care system in the United States, the VA has a particularly complex structure. This includes organizational levels (national, regional, and local leadership); settings (medical centers and community-based outpatient clinics); units (primary care, specialty outpatient, inpatient, rehabilitative); and disciplines (nursing, medicine, pharmacy, and others).…”
Section: Multisite Researchmentioning
confidence: 99%